Pengaruh Ukuran Perusahaan, Risiko Bisnis, Pertumbuhan Aset, Profitabilitas Dan Tingkat Likuiditas Pada Struktur Modal - Nurcaya, I Nyoman; adiyana, nicko sabo (E-Jurnal Akuntansi, 2015)
The purpose of this study was to determine empirically the effect of firm size, business risk, asset growth, profitability and liquidity on capital structure partially (Uj t). The sampling method with precision Slovin formula in this study was 5%, 300 samples obtained from 965 manufacturing companies in Indonesia Stock Exchange (IDX) the period of 2008-2012. This study used multiple linear regression analysis. Partial results of the study showed that the size of the company, growth in assets, profitability and liquidity and significant positive effect on the capital structure of the business risks, while significant negative effect on capital structure.
Keywords: company size, business risk, growth in assets, profitability, liquidity, and capital structure